Search for a Lorentz-violating sidereal signal with atmospheric neutrinos in IceCube - Collaboration, I; Abbasi, R; Abdou, Y; Abu-Zayyad, T; Adams, J; Aguilar, J; Ahlers, M; Andeen, K; Auffenberg, J; Bai, X; Baker, M; Barwick, S; et al. (2010)
A search for sidereal modulation in the flux of atmospheric muon neutrinos in IceCube was performed. Such a signal could be an indication of Lorentz-violating physics. Neutrino oscillation models, derivable from extensions to the Standard Model, allow for neutrino oscillations that depend on the neutrino's direction of propagation. No such direction-dependent variation was found. A discrete Fourier transform method was used to constrain the Lorentz and CPT-violating coefficients in one of these models. Due to the unique high energy reach of IceCube, it was possible to improve constraints on certain Lorentz-violating oscillations by three orders of magnitude with respect to limits set by other experiments.